Dampak Kebijakan Program Keluarga Harapan (PKH)bTerhadap Penanggulangan Kemiskinan Di Kabupaten Banjar Tahun 2013 – 2018 - Muhammad Rizaldy Nugraha; Nasruddin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
Muhammad Rizaldy Nugraha (2019), The Impact of Family Hope Program Policiesin Poverty Alleviation in the Banjar District in 2013-2018.This study aims to (1) Know the implementation of the Family Hope Program (PKH)in Banjar District. (2) Determine the impact of the Family Hope Program (PKH) policy onpoverty reduction in the Banjar District.The respondents in this study were 99 respondents from the Banjar district, and themethod used in data processing was the data tabulation method and descriptive qualitative.This study's results indicate that the Family Hope Program's policy impact onPoverty Reduction in Banjar District has a positive effect on poverty reduction. PKH policyprovides short-term and long-term benefits; in the short term, the Family Hope Programpolicy assists KSM (Very Poor Families) / RTSM (Very Poor Households) to meet theirdaily needs. And for the long term, the Family Hope program provides a variety of trainingthat will become provisions for them in the future.